Book reviews. Issue 2 (1st April 2015) - Watkinson, Anthony
Abstract : Publishing and the Advancement of Science: From Selfish Genes to Galileo's Finger Michael Rodgers London, Imperial College Press, 2014, viii + 178pp. ISBN 978‐1‐78326‐370‐7 (hbk) £50.00; ISBN 978‐1‐78326‐371‐4 (pbk) £19.00; ISBN 978‐1‐78326‐373‐8 (ebook) £19.00;www.worldscientific.com/worldscibooks/10.1142/p918